A parallel study of vibration analysis and acoustic analysis in low frequency brake noise - Phuman Singh, A.S.; Hassan, Muhammad Zahir (2012)
An acoustic analysis in the investigation of brake noise shows the severity of the noise and its characteristics, addition to a vibration analysis, which shows the excitations of noise that is present in the braking event. In this study, vibration and acoustic analysis were used to study the brake noise which is produced during braking. Vibration and acoustic data were collected simultaneously during braking to identify the braking condition. The data analysis focuses on the low frequency domain. The Fast Fourier method was used to analyse the vibration and acoustic signals. The computation of FFT was done independently and the frequency domains obtained were compared. The parallelism in the analysis was used to identify the acoustic source. The determination of the source will aid in brake noise reduction efforts and enforce the vibration analysis method as a system identification method for brake noise.